2016
DOI: 10.1016/j.ccell.2016.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Co-inhibition of CD73 and A2AR Adenosine Signaling Improves Anti-tumor Immune Responses

Abstract: Preclinical studies targeting the adenosinergic pathway have gained much attention for their clinical potential in overcoming tumor-induced immunosuppression. Here, we have identified that co-blockade of the ectonucleotidase that generates adenosine CD73 and the A2A adenosine receptor (A2AR) that mediates adenosine signaling in leuokocytes, by using compound gene-targeted mice or therapeutics that target these molecules, limits tumor initiation, growth, and metastasis. This tumor control requires effector lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
290
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 323 publications
(327 citation statements)
references
References 56 publications
10
290
0
3
Order By: Relevance
“…13,14 MEDI9447 was developed to minimize Fc-receptor (FcR) engagement; however, a recent study by Young et al identified that the anti-metastatic activities of anti-CD73 mAb were largely reliant on the ability of the mAb to engage Fc receptor, in particular, FcgRIV on CD11b C Gr-1 C myeloid cells. 11 Similar studies in the past have been instrumental in deciphering the mechanism underlying the clinical activities of anti-CTLA-4, 15,16 and anti-HER2 17 mAbs. In the current study, we assessed more extensively whether the control of primary tumors and their metastases by anti-CD73 mAbs always required the activation of Fc-receptors.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…13,14 MEDI9447 was developed to minimize Fc-receptor (FcR) engagement; however, a recent study by Young et al identified that the anti-metastatic activities of anti-CD73 mAb were largely reliant on the ability of the mAb to engage Fc receptor, in particular, FcgRIV on CD11b C Gr-1 C myeloid cells. 11 Similar studies in the past have been instrumental in deciphering the mechanism underlying the clinical activities of anti-CTLA-4, 15,16 and anti-HER2 17 mAbs. In the current study, we assessed more extensively whether the control of primary tumors and their metastases by anti-CD73 mAbs always required the activation of Fc-receptors.…”
Section: Introductionmentioning
confidence: 86%
“…Previously, we demonstrated that anti-CD73 mAb, TY/23, was able to control B16F10-CD73 hi experimental metastasis, and this required CD73 expression on tumors as well as FcgRIV engagement. 11 Work by Simpson et al had also demonstrated that different antibody isotypes can differentially bind FcR and that this influences the nature of antitumor response. 19 Given that three of our antibody clones were triple mutated in the Fc region; we investigated how treatment with these clones would impact on metastasis burden (Fig.…”
Section: Only Fcr Engaging Anti-cd73 Mabs Significantly Suppress Tumomentioning
confidence: 99%
See 3 more Smart Citations